2014
DOI: 10.1186/1471-2458-14-77
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing work participation of adults with developmental dyslexia: a systematic review

Abstract: BackgroundEvidence has been synthesized to determine hindering and facilitating factors associated with the work participation of adults with developmental dyslexia (DD), classified according to the International Classification of Functioning, Disability and Health (ICF).MethodsA systematic literature review has been performed. Two search strings were used to determine the population and the context of work. The ICF was expanded with two subdivisions: one that made the environmental factors more work-related a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 65 publications
9
80
0
3
Order By: Relevance
“…In the UK for example, around 30% of the school population fail to meet expected targets in reading or maths at age 11 (Department for Education United Kingdom, ). The long‐term outcomes for children who struggle at school include continued educational underachievement, poor mental health (Roeser & Eccles, ), and underemployment (Bynner & Parsons, ; de Beer, Engels, Heerkens, & van der Klink, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK for example, around 30% of the school population fail to meet expected targets in reading or maths at age 11 (Department for Education United Kingdom, ). The long‐term outcomes for children who struggle at school include continued educational underachievement, poor mental health (Roeser & Eccles, ), and underemployment (Bynner & Parsons, ; de Beer, Engels, Heerkens, & van der Klink, ).…”
Section: Introductionmentioning
confidence: 99%
“…These emotions often follow AWD into adulthood (Nalavany, Carwan, & Rennick, 2011;Hellendoorn & Ruijssenaars, 2000;McNulty, 2003). De Beer et al (2014) found in their seminal research that risk and protective factors influence work participation of AWD. It is not surprising that emotions about having dyslexia were one of the most frequently mentioned work-related factors cited throughout the extant research.…”
mentioning
confidence: 99%
“…Such experiences can heighten the global anxiety that is already a part of the emotional challenge that often accompanies dyslexia/ learning disability. In their systematic review of the literature, de Beer et al (2014) found that negative emotions from dyslexia were frequently voiced among the participants when reflecting upon their working lives. This finding is compelling as persistent literacy issues, keeping a job, and mostly negative emotions about dyslexia were mentioned most often in this comprehensive work.…”
mentioning
confidence: 99%
“…However, our program assesses some of the important cognitive abilities required for reading ability, besides its suitable format and accuracy (the value of 46.19 and 19.58 for auditory and visual working memories), which were both significant in distinguishing and the amount of 0.55 in differentiation in according to rapid naming task. Stanford-Binet Intelligence scale is another instance which was applied in learning disabilities prediction [31], besides estimating IQ. The previously mentioned hints are consistent in this example too.…”
Section: Discussionmentioning
confidence: 99%